Isolation and Characterization of Phosphate-Solubilizing Bacteria from Rhizospheric Soil in Suryapur, Bharatpur - Anup Muni Bajracharya; Anish Dulal (Journal of Balkumari College, 2025)
Objectives: This study was conducted to isolate and characterize phosphate-solubilizing bacteria (PSB) from rhizospheric soils of Bharatpur and to evaluate their potential in solubilizing insoluble phosphate and promoting plant growth. Methods: Soil samples were collected from nine different sites in Suryapur, Bharatpur. Pikovskaya’s agar medium was used to screen for PSB based on halo zone formation. Isolates were characterized morphologically and microscopically. The Phosphate Solubilization Index (PSI) was calculated using halo zone and colony diameters. Pot experiments were conducted to evaluate the plant growth-promoting effects of selected PSB strains on shoot and root length. Results: Out of nine sampling sites, PSB were successfully isolated from three (S1, S8, S9), yielding a total of nine isolates. Morphological and Gram-stain analyses identified both Gram-positive cocci and Gram-negative rods. PSI values ranged from 2.14 to 2.75, with isolate S9C showing the highest solubilization potential. Pot culture experiments revealed increased shoot lengths in PSB-treated plants (up to 9.5 cm) compared to controls (as low as 3.9 cm), suggesting enhanced phosphorus availability. The enhanced root length in treated plants suggests better nutrient and water absorption capability. Conclusion: The study confirms the presence of effective phosphate-solubilizing bacteria in the rhizospheric soil of Bharatpur. These isolates have potential for use as bio-inoculants to enhance phosphorus availability and support sustainable agriculture.